Analisis Pengaruh Inflasi dan Efektivitas Pemerintah terhadap Perdagangan Internasional Indonesia di Tengah Ketidakpastian Global - Anisa Putri; Taosige Wau; Miftakhul Choiri (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the effect of exchange rates, inflation, trade openness, and government effectiveness on Indonesia’s international trade amid global economic uncertainty. The study employs a quantitative approach using time series data from 2001-2025 and is analyzed using multiple linear regression. The results show that all variables simultaneously have a significant effect on international trade. Partially, inflation and government effectiveness have a significant effect, while exchange rates and trade openness do not have a significant effect. High inflation is proven to reduce international trade performance, while government effectiveness shows a negative relationship with trade activities. The insignificant effect of exchange rates and trade openness indicates that these variables have not become the main determinants of Indonesia’s international trade during the research period. These findings highlight the importance of macroeconomic stability and institutional quality in facing global uncertainty. However, this study is still limited by the use of a linear regression model and aggregate time series data, which may not fully capture the overall dynamics of international trade.